Occultist identity formations between theosophy and socialism in fin-de-siècle France - Strube, Julian (Numen, 2017)
Fin-de-siècle occultism is usually regarded within the context of an “occult revival” that implies the modernization of an older esoteric tradition. However, this notion is rooted in esoteric identificatory discourses at the end of the nineteenth century. This article will discuss two major aspects of these discourses. First, French esotericists polemically distanced themselves from the “Eastern” esotericism of the Theosophical Society by constructing an ésotérisme occidental. It will be shown that this separation of “East” and “West” occurred as a reaction to the T.S., and should thus be seen as a “nationalist” response to a global phenomenon. Second, another major aspect of occultist identity formations will be highlighted: socialism. It will be shown that fin-de-siècle occultists were deeply involved with socialist theories in the July Monarchy vein but ambiguously distanced themselves from contemporary “materialist” socialisms. An analysis of this context will further help to understand the construction of an esoteric tradition.